The combined application of human adipose derived stem cells and Chondroitinase ABC in treatment of a spinal cord injury model. (February 2017) - Sarveazad, Arash; Babahajian, Asrin; Bakhtiari, Mehrdad; Soleimani, Mansoureh; Behnam, Babak; Yari, Abazar; Akbari, Abolfazl; Yousefifard, Mahmoud; Janzadeh, Atousa; Amini, Naser; Agah, Shahram; Fallah, Ali; et al.
Abstract: Background: Although stem cell therapy has become a major focus as a new option for management of spinal cord injury (SCI), its effectiveness should be promoted. In this study, we investigated the effects of co-administrating human adipose-derived stem cells (hADSCs) and Chondroitinase ABC (ChABC) in a rat model of spinal cord injury. Material and methods: hADSCs derived from superficial layer of abdominal adipose tissue were used to treat a contusion-induced SCI. Animals were randomly allocated to five equal groups including sham (only laminectomy), SCI (SCI + vehicle injection), hADSCs (1 × 10⁶ hADSCs/10 μl intra-spinal injection), ChABC (10 μl of 100 U/ml ChABC intra-spinal injection injection), and hADSCs + ChABC. Basso, Beattie and Bresnahan tests were used to evaluate locomotor function. 8 weeks after treatment, cavity size, myelination, cell differentiation (neuron and astrocyte), and chondroitin sulfate amount were analyzed. Results: hADSC transplanted animals, ChABC injected animals (P < 0.001), and hADSC + ChABC treated rats (P < 0.001) displayed significant motor improvement compared to SCI group. Combination therapy of hADSCs and ChABC led to greater locomotor recovery compared to using hADSCs (P < 0.001) or ChABC (P < 0.01) alone. Spinal cords in the combined and single therapy groups had cavities filled with myelinated areas and less chondroitin sulfate content in comparison with the control group (P < 0.001). hADSCs expressed GFAP, B III tubulin and Map2. Conclusion: Combination therapy with ChABC and hADSCs exhibits more significant functional recovery than single therapy using either. This result may be applicable in selection of the best therapeutic strategy for SCI. Highlights: Application of human adipose derived stem cells (hADSCs) and Chondroitinase ABC (ChABC) on spinal cord injury The combination therapy of ChABC and hADSCs exhibit more significant functional recovery over any single therapy alone Co-administration of ChABC and hADSCs promote myelination and decrease amount of chondroitin sulphate after spinal cord injury